Forme processuali nella poesia italiana contemporanea: dal «gabbione» al piccolo schermo - Giulia Martini (Griseldaonline, 2023)
The present article aims to dwell on the evolution of judicial process forms in contemporary Italian poetry through the analysis and comparison of three poems that chronologically cover a century: L’Incendiario [The Firefighter] (1910) by Aldo Palazzeschi, Il giudice [The Judge] (1963) by Mario Luzi and Piccola anamnesis dell’insonnia [Little Anamnesis of Insomnia] (2008) by Carlo Bordini. The use of the dialogical expedient that associates the three texts allows us to measure the distance between the model of communication in court (Galatolo 2002) and the lyrical episodes that refer to it, declining it in various forms: it is highlighted, in particular, how the representation of the process is dislocated in increasingly private and virtual places: from the «central square | of the town» (Palazzeschi) to the bedroom (Bordini), in line with a progressive disqualification of the judicial institution and its highest representative, the judge.